Community willingness to pay for improved urban solid waste management in Malaysia : a choice modelling approach - Bashawir, Ahmad; Subhan, Muhammad; Othman, Jamal (Jurnal Ilmu Ekonomi dan Pembangunan, 2009)
This study attemps to make an analysis and assesment of public attitudes and behavior towards an improved municipal solid waste management offered by a majlis perbandaran (municipality) by looking at their willingness to pay (WTP). Majlis Perbandaran Seremban in Malaysia has been chosen for this study because of its very rapid development and economics growth factors. Our study areas include seven residential under the administration of Majlis Perbandaran Seremban. A survey and direct observation techniques have been carried out using the quistionaire to the 140 households. Contingen valuation method (CVM) is used for the analysis. Results of the study found that the mean and median value of monthly willingness to pay of the people for each households is RM 23 and RM 25 respectively.Keywords: solid waste management, contingen valuation, willingness-to-pay, choice modelling, urban management, environmental issue, Malaysia